MASA DEPAN YAMAN DALAM REKONSILIASI STABILITAS KAWASAN TIMUR TENGAH - Hadi, Herwan; Nurwahidin, Nurwahidin (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to examine Yemen's future in reconciling the stability of the Middle East region. This research uses library methods. The results of this research show that post-peace, facilitated by Saudi Arabia, Iran and China, is a new door in turning the page towards a conducive Middle East region, especially the country of Yemen itself. This reconciliation or peace occurred after experiencing a long civil war between the Sunni-dominated government group supported by Saudi Arabia and the Shia Houthi group supported by Iran, where this horizontal conflict was approximately eight years and had claimed lives and property that were not A little. An important part of the peace results that were realized and held in Iran on March 10 2023 recently was the way to end the complex problems that shackle Yemen, thereby having an overall impact on the Middle East region because this issue involves the interests of many countries.